Socioeconomic status moderates the association between perceived environment and active commuting to school - Alexandre Augusto de Paula da Silva; Rogério César Fermino; Carla Adriane Souza; Alex Vieira Lima; Ciro Romelio Rodriguez-Añez; Rodrigo Siqueira Reis (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To analyze the moderator effect of socioeconomic status in the association between the perceived environment and active commuting to school. METHODS: A total of 495 adolescents and their parents were interviewed. Perceived environment was operationalized in traffic and crime safety and assessed with the Neighborhood Environment Walkability Scale. Active commuting was self-reported by the adolescents, categorized in walking, bicycling or skating at least one time/week. Socioeconomic status was used as moderator effect, reported from adolescents' parents or guardians using Brazilian standardized socioeconomic status classification. Analyses were performed with Poisson regression on Stata 12.0. RESULTS: Prevalence of active commuting was 63%. Adolescents with low socioeconomic status who reported "it is easy to observe pedestrians and cyclists" were more likely to actively commute to school (PR = 1.18, 95%CI 1.03-1.13). Adolescents with low socioeconomic status whose parents or legal guardians reported positively to "being safe crossing the streets" had increased probability of active commuting to school (PR = 1.10, 95%CI 1.01-1.20), as well as those with high socioeconomic status with "perception of crime" were positively associated to the outcome (PR = 1.33, 95%CI 1.03-1.72). CONCLUSIONS: Socioeconomic status showed moderating effects in the association between the perceived environment and active commuting to school.